In vitro multiplication of Cedrela fissilis Vell.: A threatened brazilian hardwood forest tree - Bonfá, Yasmim Smarsaro; Nascimento, Vitor de Laia; Werner, Elias Terra (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2021)
Cedrela fissilis Vell. is a valuable wood species from Atlantic Forest and is at risk of extinction. Therefore, a protocol for plant regeneration was developed for C. fissilis using different explants from in vitro germinated plant. The seeds were germinated in total or half- strength MS and B5 basal. The half-strength MS medium was chosen because of its uniform morphological aspect, highgermination rate (82) and germination speed index (1.218). The shoot tips, nodal segments and cotyledonary nodes explants were extracted from the germinated in vitro plants and cultivated for shoot induction in MS medium supplemented with KIN or BAP (0, 0.5, 2, 4 μM). Among the different explants, cytokinins and concentrations, the highest number (2.2) and length (3.84 cm) of shoots were induced in cotyledonary nodes without cytokinin. For rooting of shoot regenerated from explants, the MS medium was supplemented with IBA or NAA (0, 1, 3 μM). Rooting was induced in all auxins type and concentrations, with higher number of roots per explant with 3μM IBA (2.54). In conclusion, the present study provides in vitro shoot and root regeneration system in C. fissilis without plant growth regulators and great potential in micropropagation, germplasm preservation and genetic transformation. Index terms: Cedro-rosa; vulnerable; cotyledonary nodes; plant growth regulator; micropropagation.